(untitled) (ModaPalavra e-periódico, 2023)
This article discusses the relationship between design and craftsmanship by analyzing the processes of productive groups in the creation of authorial pieces. Based on the experience report on the development of the Ateliê Social collections of Instituto Casa de Mãe, an attempt is made to register the method used with the objective of reflecting on issues pertinent to the local reality for the creation of poetic and aesthetic narratives, as well as for the income generation. This design direction brings to light questions about the urban craft object, its symbolism and what is the role of designers when dealing with groups of artisans. With the report of five years of collaborative collections, it is concluded that the contemporary craftsman does not act alone, but within the interaction of a web of connections willing to build a creative economy.